Exposure to Perfluoroalkyl Chemicals and Cardiovascular Disease: Experimental and Epidemiological Evidence - Meneguzzi, Alessandra; Fava, Cristiano; Castelli, Marco; Minuz, Pietro (Frontiers in Endocrinology, 2021)
Polyfluoro- and perfluoro–alkyl substances (PFAS) are organic chemicals extensively used worldwide for industry and consumer products. Due to their chemical stability, PFAS represent a major cause of environmental pollution. PFAS accumulate in animal and human blood and tissues exerting their toxicity. We performed a review of the epidemiological studies exploring the relationship between exposure to PFAS and thromboembolic cardiovascular disease. An increase in cardiovascular disease or death related to PFAS exposure has been reported from cross-sectional and longitudinal observational studies with evidence concerning the relation with early vascular lesions and atherosclerosis. Several studies indicate an alteration in lipid and glucose metabolism disorders and increased blood pressure as a possible link with cardiovascular thromboembolic events. We also examined the recent evidence indicating that legacy and new PFAS can be incorporated in platelet cell membranes giving a solid rationale to the observed increase risk of cardiovascular events in the populations exposed to PFAS by directly promoting thrombus formation. Exposure to PFAS has been related to altered plasma membrane fluidity and associated with altered calcium signal and increased platelet response to agonists, both in vitro end ex vivo in subjects exposed to PFAS. All the functional responses are increased in platelets by incorporation of PFAS: adhesion, aggregation, microvesicles release and experimental thrombus formation. These findings offer mechanistic support the hypothesis that platelet-centred mechanisms may be implicated in the increase in cardiovascular events observed in populations chronically exposed to PFAS.